OPTIMALISASI LITERASI EDUPRENEUR MELALUI GAMBAR DAMAR KURUNG UNTUK SISWA TUNARUNGU DI SLB KEMALA BAYANGKARI GRESIK - Tasaufy, Fariq Shiddiq; Camelia, Ika Anggun; Retyaningrum, Fera (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
This community service program aims to optimize edupreneur literacy among deaf students at SLB Kemala Bhayangkari Gresik by utilizing Damar Kurung artwork as both a learning medium and a creative product. The key problems identified include limited understanding of local cultural wisdom, insufficient entrepreneurial literacy, and restricted market access for students’ creative works. The program was carried out through several stages, including socialization, cultural literacy training on Damar Kurung, workshops on visual artwork production, and training on basic entrepreneurship and digital marketing. The results show significant improvement in students’ ability to recognize Damar Kurung elements, creative drawing skills, confidence in presenting their artwork, and understanding of the economic value of cultural products. Approximately 30 visual artworks were successfully produced as prototypes of creative products. Teachers also experienced improved capacity in developing culture-based instructional media and integrating entrepreneurial concepts into lesson plans. Overall, the program demonstrates that cultural and entrepreneurial literacy can be effectively cultivated through a visual, local wisdom–based approach, supporting the economic independence of deaf students and contributing to the development of the local creative economy.